Pengaruh Ekstrak Metanol Buah Lakum (Cayratia trifolia L. Domin) terhadap Nilai SGOT dan SGPT Tikus Putih Diinduksi Parasetamol - Rousdy, Diah Wulandari; Wardoyo, Elvi Rusmiyanto Pancaning; Wulandari, Catur (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Lakum fruit (Cayratia trifolia L. (Domin)) has secondary metabolite compounds that are beneficial to health, one of which is a hepatoprotector. This study was conducted to prove the potential of hepatoprotective activity of lakum fruit methanol extract based on the value of SGPT and SGOT enzyme. The research method used a pre-posttest randomized control group design with a sample of 35 male rats divided into five treatment groups: solvent control group (CMC 0.5%); positive control group (HEPA-QÂ®); treatment group extract (0,575; 1,15; 1,725 mg/g BW). The treatment of induction of paracetamol and methanol extract of Cayratia trifolia fruit was carried out for 7 days respectively. The results showed that the dose of 1,15 mg/g BW of Cayratia trifolia fruit methanol extract had the most effective deterioration of SGOT and SGPT values with a percentage reduction of SGOT of 49.3% and SGPT of 51.8% (p <0.05) which approached control positive (HEPA-QÂ®). Based on the research conducted, methanol extract of Cayratia trifolia fruit has the potential to be hepatoprotective.